The Internet

Log In or Register

To find the nth term of the given geometric sequence, we can observe the pattern in the sequence. The first term \( a_1 \) is \(-4\) and each subsequent term is multiplied by \(-4\) (i.e., \(-4 \times -4 = -16\), \(-16 \times -4 = -64\), etc.).

Thus, the general formula for the nth term of a geometric sequence can be represented as:

\[
a_n = a_1 \cdot r^{(n-1)}
\]

In this case, \( a_1 = -4 \) and the common ratio \( r = -4 \). Therefore, the formula for the nth term is:

\[
a_n = -4 \cdot (-4

Finding the nth term of a geometric sequence

Bookmark

0 Points

▲ good image

bad image ▼

Ask AI on The Internet

Question: The first six terms in a geometric sequence are shown, where a1 = – 4. – 4 – 16 – 64 – 256 – 1,024 – 4,096 . . . Based on this information, which equation can be used to find the nth term in the sequence, an? A. an = – (4)n B. an = – 4n C. an = (– 4)n D. an = – n2

Asked by abdul1

0 Points

Log In or Register to Vote

In a geometric sequence, each term is found by multiplying the previous term by a constant ratio. Let's check the ratio for the given sequence: Given the sequence: \[ -4, -16, -64, -256, -1024, -4096 \] To find the common ratio (\( r \)), divide the second term by the first term: \[ r = \frac{-16}{-4} = 4 \] To confirm this, let's check the ratio between subsequent terms: \[ \frac{-64}{-16} = 4 \] \[ \frac{-256}{-64} = 4 \] \[ \frac{-1024}{-256} = 4 \] \[ \frac{-4096}{-1024} = 4 \] It is consistent, so the common ratio is \( 4 \). The formula for the nth term (\( a_n \)) in a geometric sequence is: \[ a_n = a_1 \cdot r^{n-1} \] Where: - \( a_1 \) is the first term - \( r \) is the common ratio - \( n \) is the term number Given \( a_1 = -4 \) and \( r = 4 \): \[ a_n = -4 \cdot 4^{n-1} \] Let's review the given answer choices: A. \( a_n = -(4)^n \) B. \( a_n = -4n \) C. \( a_n = (-4)^n \) D. \( a_n = -n^2 \) Among these choices, choice A can be rewritten and simplified to match our sequence's formula: \[ a_n = -(4^n) \] This is the same as: \[ a_n = -4 \cdot 4^{n-1} \] Because, \[ -(4)^n = -4 \cdot 4^{n-1} \] Thus, the correct equation to find the nth term in the sequence is: **A. \( a_n = -(4)^n \)**

Answered by gpt-4o

Feb. 4, 2025, 6:41 a.m.

0 Points

Log In or Register to Vote

Think your answer is better than the AI's? Post it below.

Please log in or sign up to post your answer.

Question Tags
This article was generated in part by one of OpenAI’s large-scale language-generation model, answering user abdul1's question. Images were generated with OpenAI's AI model, DALL·E 3. The Internet takes ultimate responsibility for the content of this publication.
If you want your question answered by an AI, click here.

Published: Tuesday, February 4, 2025

Comment Section

Post your own comment: